Intonation Maxims Role in Utterance Meaning (Journal of the College of Basic Education, 2023)
It is generally known that intonation or the pitch of an utterance plays a major role in assigning utterance meaning .According to this role; a certain classification can be attributed to utterance type in the light of its meaning. The present study shows how intonation maxims play their role in assigning utterance meaning and what classification they lend utterances according to that role .They make a close relation between an utterance and its implicit meaning in the same way that Grice maxims relate between and utterances and their implicit meanings .The relation is to be shown towards the application of these roles in to the selected data chosen as extracts of questioning conversation .